2013
DOI: 10.1126/science.1243147
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic Volume Modulates Spindle Size During Embryogenesis

Abstract: Rapid and reductive cell divisions during embryogenesis require that intracellular structures adapt to a wide range of cell sizes. The mitotic spindle presents a central example of this flexibility, scaling with the dimensions of the cell to mediate accurate chromosome segregation. To determine whether spindle size regulation is achieved through a developmental program or is intrinsically specified by cell size or shape, we developed a system to encapsulate cytoplasm from Xenopus eggs and embryos inside cell-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
278
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 240 publications
(308 citation statements)
references
References 37 publications
19
278
2
1
Order By: Relevance
“…Most intriguingly, the spindle size scales linearly with the cell size up to a certain limit; and such a biphasic scaling relationship, as well as the critical cell size and spindle size for the biphasic transition, appear surprisingly consistent across metazoan species (5,8,10). Such size scaling is also partially reproduced in in vitro spindle reconstitution experiments (15,16). From the physics point of view, such universal size-scaling phenomena are highly significant, as they suggest intrinsic principles in the spatial organization of the mitotic spindle.…”
Section: Introductionmentioning
confidence: 75%
“…Most intriguingly, the spindle size scales linearly with the cell size up to a certain limit; and such a biphasic scaling relationship, as well as the critical cell size and spindle size for the biphasic transition, appear surprisingly consistent across metazoan species (5,8,10). Such size scaling is also partially reproduced in in vitro spindle reconstitution experiments (15,16). From the physics point of view, such universal size-scaling phenomena are highly significant, as they suggest intrinsic principles in the spatial organization of the mitotic spindle.…”
Section: Introductionmentioning
confidence: 75%
“…This characteristic mitotic cell shape provides a geometrical boundary that both restricts and directs spindle size and orientation 35,36 . Microfluidic techniques, provide a level of geometrical confinement that accurately resembles the situation observed in living cells and therefore permits the bottom-up reconstruction of mitotic spindles in vitro.…”
Section: Representative Resultsmentioning
confidence: 99%
“…In addition, growing into a physical barrier can induce microtubule catastrophes. Also, spindle assembly within a confined geometry can lead to a gradual depletion of individual components, such as tubulin, which in turn directly affects the microtubule growth rate 36 . These are all essential determinants of spindle assembly, which can be studied using the assays described here.…”
Section: Discussionmentioning
confidence: 99%
“…Changing spindle size in developing embryos had no effect on chromosome segregation, but interfered with spindle orientation, suggesting that it is coupled to cell size through a ratiometric mechanism controlling microtubule destabilization. This idea was further explored via an innovative system, in which Xenopus egg extracts were encapsulated using microfluidic technology (99,100). Both studies beautifully demonstrated that reductions in cytoplasmic volume, rather than developmental cues or changes in cell shape, were sufficient to recapitulate spindle scaling observed in Xenopus embryos.…”
Section: Assembly and Scaling Of Self-organized Microtubule Structuresmentioning
confidence: 99%